Building Trading Bots Using Java - Varshney, Shekhar (Apress : Imprint: Apress, 2016)
This book will take you on an exciting journey of building an automated currency trading bot from scratch. On this journey, you will learn not only about the nitty-gritty of automated trading, but with the help of numerous code samples, have a closer look at Java, Spring Framework, Event Driven programming and other open source APIs, notably Google's Guava API. And of course, it will all be test driven with unit testing coverage. The central theme of the book is to aim to create a framework which can facilitate automated trading on most of the brokerage platforms, with minimum changes. At the end of the journey, we should have a working trading bot, with a sample implementation using the OANDA REST API, which is free to use. Over the course of this book, you will learn the following: What is a trading bot What are trade-able instruments and how to apply bots to them How to track and use market data events How to place orders and trades How to work with trade/order and account events.